Mere Christianity: a revised and amplified edition, with a new introduction, of the three books, Broadcast talks, Christian behaviour, and Beyond personality - Lewis, C. S. (HarperOne, 2001)
This book is one of the most popular introductions to Christian faith ever written. Mere Christianity has sold millions of copies worldwide. The book brings together C. S. Lewis's legendary broadcast talks of the war years, talks in which he set out simply to "explain and defend the belief that has been common to nearly all Christians at all times." Rejecting the boundaries that divide Christianity's many denominations, Lewis provides an unequaled opportunity for believers and nonbelievers alike to hear a powerful, rational case for the Christian faith. It is a collection of scintillating brilliance that remains strikingly fresh for the modern reader and at the same time confirms C. S. Lewis's reputation as one of the leading writers and thinkers of our age. - Jacket flap